ELEMENTAL ANALYSIS OF CULINARY HERBS AND SPICES BY ICP OES: CLASSIFICATION BY CHEMOMETRICS - PAVLOVIĆ, Aleksandra N.; MRMOŠANIN, Jelena M.; JOVANOVIĆ, Snežana Č.; MITIĆ, Snežana S.; TOŠIĆ, Snežana B.; KRSTIĆ, Jovana N.; STOJANOVIĆ, Gordana S. (Studia Universitatis Babeș-Bolyai Chemia, 2020)
The inductively coupled plasma optical emission spectrometry method (ICP OES) was optimized and validated for the quantification of 21 elements in 88 samples of 23 types of culinary herbs and spices. All analyzed samples were low in Na, but rich in Ca, K and P. Among the microelements, the most abundant was Fe, followed by Cu, Zn, Cr, and Se. The concentrations of toxic elements (Cd and Pb) were below the permissible limits given by the World Health Organisation (WHO). Chemometrics was performed by the principal component analysis (PCA) and cluster analysis (CA). PCA generated two principal components that explained 43.82% of the total variance in the data and all samples were classified into six groups based on the element content. Also, PCA and CA allowed the differentiation and classification of culinary herbs and spices based on the concentration of five major elements.